“Auditoría de Gestión a la Cooperativa de Ahorro y Crédito COORCOTOPAXI, Agencia La Maná, cantón La Maná, periodo 2018” - Díaz Faz, María Nelly (2020)
One of the reasons to do a management audit is the need to control the management in an organization in various areas, with the objective of establishing a control of efficiency and effectiveness. Therefore, it was considered necessary to execute a management audit of the COORCOTOPAXI Credit Union, La Maná branch office, period 2018, to determine its current status and take measures to improve its efficiency and effectiveness. Among the types of research used are bibliographic, field, quantitative, qualitative and descriptive research; the methods used include the inductive, deductive, analytical and scientific together with the technique of the interview and surveys. In the first instance, the preliminary knowledge phase was carried out, which included the description of the of the entity’s data, history, mission, vision, corporate values, objectives, description of financial products and services, structural organization chart, financing method, legal basis, audit request, commitment letter and SWOT analysis. In the planning process the scope, methodology and audit program was established. The application of internal control reflected a management audit risk of 1.23%, which is a low risk. The findings detected through the Management Audit were: low dissemination of strategic planning, low level of staff training, lack of knowledge of the partners about the services provided by the cooperative, the goal of reducing the delinquency index set for the microenterprise credit line. Once the management indicators were applied, 78% were evidenced for the efficiency indicator, 61% at the level of effectiveness; giving a percentage of 78% effectiveness. In view of the findings described, their recommendations were proposed, which must be complied with the collaborators of the entity, in order to reduce future risks that are latent in various areas of the Credit Union COORCOTOPAXI, La Maná branch office.